2010
DOI: 10.1371/journal.pone.0012478
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Cause Disability and Axon Loss in a Mouse Model of Multiple Sclerosis

Abstract: BackgroundThe objective of this study was to test the hypothesis that CD8+ T cells directly mediate motor disability and axon injury in the demyelinated central nervous system. We have previously observed that genetic deletion of the CD8+ T cell effector molecule perforin leads to preservation of motor function and preservation of spinal axons in chronically demyelinated mice.Methodology/Principal FindingsTo determine if CD8+ T cells are necessary and sufficient to directly injure demyelinated axons, we adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 30 publications
2
40
1
Order By: Relevance
“…In agreement with the present findings, β-APP-positive axons can be detected predominately in acute MS lesions and less frequent associated with chronic plaques [6,44,45]. In TME, the onset of axonopathy in the spinal cord during the initial stage is suggested to be a virus-induced effect [10] while axonal degeneration and loss at the later stages is more related to an immune-mediated attack [8,46,47], and a lack of glial-derived trophic support which induces neurodegenerative mechanisms in vulnerable, demyelinated axons [48]. Axonal degeneration is regarded as an active self-destructive response to TMEV infection to prevent further axonal spread of the virus [49].…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with the present findings, β-APP-positive axons can be detected predominately in acute MS lesions and less frequent associated with chronic plaques [6,44,45]. In TME, the onset of axonopathy in the spinal cord during the initial stage is suggested to be a virus-induced effect [10] while axonal degeneration and loss at the later stages is more related to an immune-mediated attack [8,46,47], and a lack of glial-derived trophic support which induces neurodegenerative mechanisms in vulnerable, demyelinated axons [48]. Axonal degeneration is regarded as an active self-destructive response to TMEV infection to prevent further axonal spread of the virus [49].…”
Section: Discussionsupporting
confidence: 87%
“…Perforin has been reported as a key mediator in the CTL-induced axonal/neuronal damage in various mice models of autoimmune diseases (53)(54)(55)(56)(57). In contrast, our study showed that GrB internalization into neurons as well as purified GrB and T cellmediated neuronal killing are independent of perforin (Figs.…”
Section: Discussioncontrasting
confidence: 67%
“…CSF levels of granzyme B (GzB) correlate with relapse rate in a sub-population of MS patients 23 and animal models of MS link CTL effector functions to axon loss and development of neurological deficits. In the Theiler’s murine encephalomyelitis model, genetic deletion of perforin (PFP) or the disruption of MHC-I surface expression by genetic deletion of β2-microglobulin result in protection of axons and preservation of neurologic function, despite extensive CNS demyelination 24-27 .…”
Section: Introductionmentioning
confidence: 99%